Review of Management, Maternal and Fetal Outcomes in Women with Eclampsia in Kogi Eastern Hospitals, North Central Nigeria - Akogu, Simon Peterside Onuche; Omoniyi, Musa Abdulkarim; Ekpe, Christian; Idachaba, Timothy; Alakpo, Funmilola (British Journal of Healthcare and Medical Research, 2024)
Introduction: Eclampsia is defined as the occurrence of convulsion with the syndrome of preeclampsia. Pre-eclampsia is a multi-systemic disease typified by raised blood pressure and proteinuria [1, 2, 3, 20]. This study reviewed Eclampsia management protocols including patients care instructions, oxygen administration, use of antihypertensive, anticonvulsant, maternal outcome and neonatal outcome. This type of enquiry will generate information that will stimulate systems wide appraisals for improvement in the management of Eclampsia. Material and Methods: This is a retrospective case series study. Case files of consecutive cases of eclampsia managed between January 2018 and December 2022 in the 5 hospitals in Kogi East, North central Nigeria were extracted. Using a structured questionnaire, information on bio data, relevant obstetrics characteristics, case management and outcome were obtained and analyzed. Results: Majority of parturient are in the age range of 20 – 34 years (43.7%). There were 3321 deliveries. 135 of the women had eclampsia while 11 women died from complications of eclampsia. The maternal mortality ratio due to eclampsia is 332 per 100,000 live births. The case fatality rate for eclampsia in this study is 8.2%, the incidence of eclampsia is 41 case per 1000 live births. This review of the management of Eclampsia showed sub optimal practices. Conclusion: The incidence of eclampsia, the case fatality rate and maternal mortality due to eclampsia are unacceptably high compare to the developed societies [1, 2]. We need to improve on maternity services for antenatal care, positive pregnancy experience and early intervention.